2019
DOI: 10.3389/frwa.2019.00002
|View full text |Cite
|
Sign up to set email alerts
|

Social Comparison as a Tool to Promote Residential Water Conservation

Abstract: Many regions around the world experience both chronic and intermittent needs for residents to reduce their water consumption. Recent advances in water metering infrastructure offer opportunities to provide customers with detailed feedback about their consumption, but research in behavioral science suggests that feedback by itself is not enough to motivate conservation. The current empirical work builds on previous studies showing the ability of an augmented feedback approach to promote reductions in residentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 18 publications
(21 reference statements)
1
25
2
Order By: Relevance
“…Our results were not supportive of this hypothesis, suggesting that there was no difference in the amount of change for different referent group comparisons at different levels below the norm. This was inconsistent with research showing this hypothesized effect for water conservation and energy use intentions and their difference for very high consumers (Bergquist & Nilsson, 2018;Schultz, 2019). However, this is one of the first studies to test the differences in the specificity of the norm referent group so comparisons to previous literature should be interpreted with caution.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Our results were not supportive of this hypothesis, suggesting that there was no difference in the amount of change for different referent group comparisons at different levels below the norm. This was inconsistent with research showing this hypothesized effect for water conservation and energy use intentions and their difference for very high consumers (Bergquist & Nilsson, 2018;Schultz, 2019). However, this is one of the first studies to test the differences in the specificity of the norm referent group so comparisons to previous literature should be interpreted with caution.…”
Section: Discussioncontrasting
confidence: 59%
“…In addition to the need for research testing the relative impact of different referent groups, it is also important to examine the behavioral response of individuals with varying levels of deviation from the norm. Prior research has shown a differential pattern of responses for individuals who are above or below the referent group norm in both energy and water conservation (Schultz, 2019;Schultz et al, 2008). Bergquist and Nilsson (2018) hypothesized a 'norm distancing effect', which suggests that people are more likely to adjust their behavior to conform to the norm if the discrepancy between the two is small.…”
Section: Current Studymentioning
confidence: 99%
“…For example, the number of waste bags you produced during a certain period compared to the number of waste bags your neighbours on average produced during the same period. Numerous studies have shown that social comparison feedback promotes pro-environmental behaviour, for example, energy conservation [23][24][25][26][27][28], water conservation in households [29][30][31], and food waste recycling [32]. Research also suggests that social comparison feedback promotes waste recycling and reduces sorting errors, compared to general persuasive information [17].…”
Section: Feedback and Comparison Standardsmentioning
confidence: 99%
“…Research also suggests that social comparison feedback promotes waste recycling and reduces sorting errors, compared to general persuasive information [17]. However, a study found that social comparison feedback did not reduce water and energy consumption [31]. The authors suggested that the comparative others should be socially meaningful to the participants (i.e., a pre-existing social group or similar others).…”
Section: Feedback and Comparison Standardsmentioning
confidence: 99%
See 1 more Smart Citation